2019
DOI: 10.21608/jappmu.2019.53492
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Nutrients Digestibility and some Blood Constituents in Growing New Zealand White Rabbits Fed Diets Supplemented with Eucalyptus globules

Abstract: This study was conducted to investigate the effects of supplementing the rabbit diets with Eucalyptus globulus dried leaves (EGL) or its aqueous extract (EGE) on growth performance, nutrients digestibility and blood constituents. A total number of 225 weaned New Zealand White rabbits, six weeks old, were used in this experiment. Treatment groups were ; a control diet (C), T 1 and T 2 were the control diet + 0.25 or 0.5% dried eucalyptus leaves, respectively, T 3 and T 4 were the control diet + 0.05 or 0.1% aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…They found that there was no significant difference due to eucalyptus supplementation on FCR. Different results were found by [71] in terms of body gain and feed intake, where they found that body gain of rabbits supplemented with eucalyptus showed greater gain and lower feed intake. They added that FCR was improved as eucalyptus levels increased.…”
Section: Effect On Productivity Performancementioning
confidence: 79%
See 2 more Smart Citations
“…They found that there was no significant difference due to eucalyptus supplementation on FCR. Different results were found by [71] in terms of body gain and feed intake, where they found that body gain of rabbits supplemented with eucalyptus showed greater gain and lower feed intake. They added that FCR was improved as eucalyptus levels increased.…”
Section: Effect On Productivity Performancementioning
confidence: 79%
“…They added that adding eucalyptus to the diets of rabbits is considered safe until 13.5 percent. In addition, [71] found that there was no effect of supplementation with eucalyptus on the AST and ALT activities in growing rabbits.…”
Section: Hematological Parameters and Blood Biochemistry Constituentsmentioning
confidence: 97%
See 1 more Smart Citation